H2O·HF@C70: Encapsulation Energetics and Thermodynamics - Zdeněk Slanina; Filip Uhlík; Xing Lu; Takeshi Akasaka; Ludwik Adamowicz (Inorganics, 2023)
This report deals with the quantum-chemical evaluation of the energetics and thermodynamics of the simultaneous encapsulation of HF and H<semantics>2</semantics>O by the IPR (isolated pentagon rule) C<semantics>70</semantics> fullerene cage, yielding <semantics>H2O·HF@C70</semantics> species which were synthesized and characterized recently, thus further expanding the family of fullerene endohedrals with non-metallic encapsulates. The structures were optimized at the DFT (density functional theory) M06-2X/6-31++G** level. The encapsulation energetics were further refined by the advanced B2PLYPD/6-31++G** and B2PLYPD/6-311++G** methods. After enhancement of the B2PLYPD/6-311++G** encapsulation energy for the BSSE and steric corrections, the encapsulation energy gain was obtained, as 26 kcal/mol. The equilibrium encapsulation thermodynamics were described using the M06-2X/6-31++G** partition functions. The results correspond to our previous evaluations for the water dimer encapsulation by C<semantics>84</semantics> cages.